INDONESIA’S ELECTRONIC MONEY LANDSCAPE: BETWEEN EFFECTIVITY AND INCLUSIVITY - Mahardika, Zahrashafa (Bank Indonesia, 2025)
Technology has transformed payment systems. Regulated digital money transactions are replacing traditional cash transactions. However, policy frameworks on payment systems often neglect to consider the diverse needs of society despite the critical role that payment systems play in society. This can be seen by the increasingly mandatory use of electronic money, which may exclude groups who have relied on traditional cash transactions but have unequal technological access. This paper explores the importance of electronic money accessibility from the perspective of Indonesian court decisions. This study reveals that current implementations, policies, and court decisions regarding electronic money have mainly focused on effectiveness rather than inclusivity. Electronic money was created to help unbaked people access financial services. However, ensuring people have technological access to these services must include everyone. This study recommends that policymakers ensure that electronic money services are accessible to the unbanked and those with limited technology access when promoting their use. On top of that, the government must also reinforce that using rupiah, in any form, remains a legal means of payment and must be respected in all transactions.